Structural, Spectroscopic and Optical Properties of Monohydrated Adenine: A Theoretical Study (Dhaka University Journal of Science, 2016)
The structural, spectroscopic (IR, NMR and UV-Vis), electronic and optical properties of monohydrated adenine (monohydrated 6-aminopurine, C5H5N5.H2O) are investigated theoretically using DFT/B3LYP level of theory. Three minimum energy structures have been identified for monohydrated of adenine where H2O molecule is doubly hydrogen bonded with adenine.1H NMR analysis shows that the protons which are hydrogen bonded become deshielded and chemical shift moves to the higher frequency region.Five IR active mode of vibrations were found at 3108, 3295, 3665, 3676 and 3719 cm-1 which are assigned as bonded -OH vibration of H2O, Bonded -NH vibration of NH2, Free -NH vibration of adenine (9 N), Free -NH vibration of NH2, Free -OH vibration of H2O, respectively and agree well with the available experimental results. The investigation of electronic properties shows that the HOMO-LUMO band gap energy of monohydrated adenine at B3LYP level is 5.15 eV. The major electronic transition (from HOMO to LUMO (83%) (π→π*)) occurs at 258 nm (4.80 eV) with a minor transition at 237 nm (5.23 eV). Theoretically it is observed that the HOMO-LUMO band gap energy is for monohydrated adenine is lower than that of adenine.Dhaka Univ. J. Sci. 64(2): 157-161, 2016 (July)